Curriculum Innovation and Communicative Language Teaching (CLT): EFL Teachers' Attitudes Towards CLT's Main Principles - Zendah, Ali Abedlqader Ali (Journal Of Education And Teaching Learning (JETL), 2025)
Curriculum innovation fosters a change in methods and investigating teachers' attitudes plays a crucial role in its successful implementation (Richards, 2015). This study explores the EFL teachers’ attitudes towards Communicative Language Teaching (CLT) across curriculum innovation in the Gaza preparatory schools' context. The study addresses two key questions: (1) What are the EFL teachers’ attitudes towards the main principles of CLT? (2) What are the potential implications of these teachers’ attitudes towards the main principles of CLT in terms of implementing CLT and teachers’ awareness of the main aspects of CLT? To answer these questions, a questionnaire was used for data collection. The collected data were analyzed through means and percentages using SPSS v17.0 statistical package. Findings reveal teachers generally hold mildly favourable attitudes towards CLT. They strongly favoure CLT's principles that emphasize the role of the learner and the importance of error correction. Meanwhile, they are moderately favourable towards teacher's role and pair/group work activities. However, their attitudes towards the place and importance of grammar are less favourable. These findings suggest that many teachers may not be fully aware of CLT''s principles and may face some contextual difficulties adopting them. It is, therefore, recommended that curriculum developers and other Palestinian educational concerned bodies should take into account teachers’ attitudes in the process of change of materials and methods. Furthermore, when introducing the innovation, it is necessary to consider the cultural and social circumstances in which it operates, so that CLT may fit well within the Gaza preparatory schools' context.